E-band reconfigurable polarizer for waveguide fed antennas - Cooper, Joshua; Vijayamohanan, Jayakrishnan; Ardelean, Emil; Lane, Steven A.; Christodoulou, Christos (Frontiers in Antennas and Propagation, 2025)
A new design for a reconfigurable polarizer integrated E band horn antenna is proposed in this paper. The reconfigurable polarizer consists of two septum based waveguides which can be arranged in different configurations. Depending on the orientation of the waveguides relative to each other the desired polarization can be achieved among Linear, Right-handed circular and Left-handed circular polarization. The polarizer is integrated with a horn antenna and optimized to work from 60 to 90 GHz. This antenna is fabricated, and measured for different frequencies. The proposed design has a line of sight Axial Ratio (AR) around 1 dB and a 3 dB AR beamwidth of 56O at the center frequency.